2022
DOI: 10.1186/s13017-022-00443-x
|View full text |Cite
|
Sign up to set email alerts
|

Acute mesenteric ischemia: updated guidelines of the World Society of Emergency Surgery

Abstract: Acute mesenteric ischemia (AMI) is a group of diseases characterized by an interruption of the blood supply to varying portions of the intestine, leading to ischemia and secondary inflammatory changes. If untreated, this process may progress to life-threatening intestinal necrosis. The incidence is low, estimated at 0.09–0.2% of all acute surgical admissions, but increases with age. Although the entity is an uncommon cause of abdominal pain, diligence is required because if untreated, mortality remains in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
136
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 109 publications
(183 citation statements)
references
References 146 publications
(160 reference statements)
0
136
0
Order By: Relevance
“…Intestinal necrosis is often suggested if paracentesis draws nonclotting fluid. If diagnosis is difficult, early exploratory laparotomy or laparoscopy is not only a reliable diagnostic method but also a treatment method [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Intestinal necrosis is often suggested if paracentesis draws nonclotting fluid. If diagnosis is difficult, early exploratory laparotomy or laparoscopy is not only a reliable diagnostic method but also a treatment method [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Blind observation or conservative treatment will cause the best time for treatment to be missed. Treatments for SMAE include general treatment, surgery or endovascular therapy [ 14 ]. In terms of drug therapy, anticoagulants, fluid replenishment increasing visceral perfusion, drugs relieving mesenteric vasospasm and broad-spectrum antibiotics should be immediately administered if drug contraindications are excluded [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, once the pathology results came back negative, we were left with no other known modalities of endoscopic evaluation of diarrheal diseases [ 6 , 11 ]. We then opted to repeat a CT scan with intravenous contrast revealing atherosclerotic disease burden [ 12 , 13 ] and this allowed us to discover that the patient was suffering from CMI.…”
Section: Discussionmentioning
confidence: 99%
“…During conditions of ischemic hypoxia, such as bowel ischemia, oxygen-deprived cells will adopt anaerobic glycolysis, and the level of serum lactate will rise [ 8 , 11 ]. Studies have suggested its potential as a biomarker of intestinal ischemia [ 12 , 13 ], and the World Society of Emergency Surgery (WSES) guidelines for the management of acute mesenteric ischemia state that while no laboratory parameters are sufficiently accurate to conclusively identify ischemic bowel, elevated L-lactate may assist [ 14 ]. This study aimed to evaluate the utility of serum L-lactate as a predictor of bowel ischemia in patients with intestinal obstruction.…”
Section: Introductionmentioning
confidence: 99%